Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (Journal of Alzheimer's disease, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p < 0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: mapování mozku; lacunar infarction; Male; Stroke, Lacunar; magnetická rezonanční tomografie; Brain; kognitivní dysfunkce; lakunární cévní mozková příhoda; Amplitude of low-frequency fluctuation; Aged; mužské pohlaví; senioři; Cognitive Dysfunction; Rest; regional homogeneity; odpočinek; Neuropsychological Tests; senioři nad 80 let; mild cognitive impairment; Brain Mapping; lidé; ženské pohlaví; Humans; Aged, 80 and over; mozek; neuropsychologické testy; Magnetic Resonance Imaging; Female; lidé středního věku; Middle Aged